PSO_PI Controller of Robotic Grinding Force Servo System - Adnan Jabbar Attiya; Yang Wenyu; Salam Waley Shneen (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
When an industrial robot is used to grind a curved surface ,as marine propeller surface, contact force and feed movement must controlled together at the similar time in order that the grinding tool would machine the work-piece, with  required  force, at  the  right  position  in  right  posture. A passive wrist system  is advanced, in  this  paper, to conform the shape of the machining propeller by altering its posture along with the surface. Grinding force is controlled under a simple new PSO-PI controller at a steady value in the normal direction of the mentioned machining point by multi-point machining, while the grinding tool moving along the curved surface of the propeller. It means that the model of the passive wrist system and the surroundings could be used in force controlling when robots grind marine propeller surface by a grinding tool with multi-point machining. PSO_PI controller  policy is being assembled and compared with a PI controller to obtain a controller that provides grinding with higher quality. The compared controllers have been optimized together with the parameters of the Two-Phase Hybrid Stepping Motor. The particle swarm optimization (PSO) method was selected from several methods to optimize of Proportional-Integral controller parameters in order to give better performance with improved step response for robotic grinding force servo system and overshoot are reduced. This control method was simulated using MATLAB/SIMULINK.